Thermomechanical treatment of super high strength Cu-8.0Ni-1.8Si alloy - 潘志勇 汪明朴 李周 肖柱 陈畅 (Transactions of Nonferrous Metals Society of China, 2007)
The microstructures and properties of Cu-8.0Ni-1.8Si alloy subjected to different heat treatments were examined by mechanical and electrical properties measurements, optical and transmission electron microscopes observation. The results show that the precipitation process during aging can be accelerated by the cold deforming before aging. As the Cu-8.0Ni-1.8Si alloy is subjected to solution treatment at 970 ℃ for 4 h, cold rolling to 60% reduction, and then aging at 450 ℃ for 60 min, its properties are σb=1 050 MPa, σ0.2=786 MPa, δ=3.2% and conductivity 27.9%（IACS）. The strengthening mechanisms of the alloy include spinodal decomposition strengthening, ordering strengthening and precipitation strengthening. The precipitation of the alloy is nano-scale Ni2Si phase.